Analysis Of Production Factors That Support The Competitiveness Of Onion Farming In Risa Village, Woha District Bima Regency - Endang Asmawati; Muh Rizal S; Andi Muhammad Rivai (Public Resource Innovation Management and Excellence, 2024)
This study aims to determine what production factos support the competitiveness of onion farming in Risa Village, Woha district, Bima regency. The number of informants in this study amountend to 6 people. This type of research is descriptive qulitative research with data collection teachniques of observation, interview, and documentation. The data analysis teachnique in this study uses data collection, presenting data and drawing conclusions. The results of the study indicate that the factors that influence the production of shallot farming, starting from a large enough agricultural land for planting shallots, labor is very much needed, both machine labor, rushed labor and family labor, the use of capital in activities. Production is also very important with capital production activities can run well, the use of fertilizers and pesticides can also help in the production of shallots help eradicate pests/diseases and can help the growth and development of shallot plants, the use of seeds to produce shallots is very important, good use Superior seeds can also produce quality shallots. Then the result is that the shallots in Risa Village can be regarded as quality shallots and can compete outside the Bima area. This is supported by data obtained from farmers where the produce from farmers in Risa Village can be sold outside the area, both shallots for consumption and shallots for seeds